Exploring Health Science Students' Experiences of Learning Management Systems: Through the Lens of the Community of Inquiry Framework - Dwi Raharjo, Untoro; Praptana , Praptana; Hernawan, Heri; Markus, Suryo Nugroho; Ariningtyas , Ristiana Eka; Prahesti, Ratna (Journal of health research and technology, 2024)
The digital revolution in education, particularly in higher education, has led to the widespread adoption of online learning platforms like Learning Management Systems (LMS). The Faculty of Health at Universitas Jenderal Achmad Yani Yogyakarta has embraced this trend, employing Moodle for blended learning. However, there has been a lack of formal evaluation of students' experiences with the LMS. This research aims to fill this gap by comprehensively evaluating the user experience and learning experience of students within the Faculty of Health using the Community of Inquiry (CoI) framework. The study collected data from 201 respondents and analyzed their experiences across various CoI domains. Results indicated positive perceptions of teaching presence, social presence, and cognitive presence, with teaching presence scoring the highest. However, social presence remained the lowest aspect, highlighting the need for more personalized engagement on the LMS. While the study identified areas for improvement, it also underscored the LMS's potential in modern learning and its role in enhancing the flexibility of higher education. Further research was recommended to address the study's limitations and continue improving online learning experiences on the LMS.